Coping strategies and quality of life: a longitudinal study of high-grade glioma patient-caregiver dyads - Baumstarck, Karine (Health Qual Life Outcomes, 2018)
BACKGROUND: Among a sample of patient-informal caregiver dyads in the specific context of new diagnoses of high-grade glioma in the time-frame between diagnosis and the third month following diagnosis, we examine whether the coping strategies implemented by the patients and their caregivers influenced their own quality of life (QoL) and the QoL of their relatives. METHODS: Thirty-eight dyads with patients having recent diagnoses of high-grade glioma were involved in this longitudinal study. The self-reported data include QoL (Patient-Generated Index, EORTC QLQ-C30, and CareGiver Oncology Quality of Life), and coping strategies (BriefCope). Data were collected at T1 corresponding to the time-frame between diagnosis and postsurgical treatment initiation and T2 corresponding to the 3-month post-inclusion follow-up. RESULTS: Coping strategies based on social support and avoidance were the least used at baseline and the 3-month follow-up, both for patients and caregivers. At the 3-month follow-up, the use of social support at baseline was significantly related to lower scores of QoL for the patients and with higher QoL for the caregivers. For the patient, the use of problem-solving or positive thinking at baseline was not related to his/her QoL, while it was related to more satisfactory QoL scores for the caregiver. The use of avoidance at baseline was linked to a higher 3-month QoL for the patients and a lower 3-month QoL for the caregivers. Using the specific dyadic analyses (actor–partner interdependence model), the 3-month patient’s QoL was lower (β = − 0.322; p = 0.03) when the patient mobilized the social support strategy at baseline, but was higher(β = 0.631; p < 10(− 3)) when his/her informal caregiver used this strategy. After adjustment for sex, age, and baseline PGI score, the link between high use of the social support strategy at baseline by the caregiver and the patient’s 3-month QoL, remained present (positive partner effect; β =0.675; p < 10(− 3)). CONCLUSION: The QoL for patients and their informal caregivers since the time of diagnosis is directly related to the use of coping strategies based on social support at time of diagnosis.